Impact of deficit irrigation on sorghum physical and chemical properties and ethanol yield - Liu, Liman; Maier, Anne; Klocke, Norman L.; Yan, Shuping; Rogers, Danny H.; Tesso, Tesfaye T.; Wang, Donghai (My University)
The objective of this research was to study the effect of irrigation levels (five levels from 304.8 to 76.2 mm water) on the physical and chemical properties and ethanol fermentation performance of sorghum. Ten sorghum samples grown under semi-arid climatic conditions were harvested in 2011 from the Kansas State University Southwest Research-Extension Center near Garden City, Kansas, and evaluated. Irrigation had a significant effect on the physical properties, chemical composition, ethanol yield, and fermentation efficiency of sorghum. Sorghum kernel hardness increased and test weight decreased as the irrigation level decreased. Starch contents of sorghum samples grown under a low irrigation level were approximately 7% less than those grown under a high irrigation level. Protein contents ranged from 9.84% to 14.91% and increased as irrigation level decreased. Starch pasting temperature increased significantly, and starch peak pasting viscosity and setback viscosity decreased as the irrigation level decreased. Free amino nitrogen (FAN) increased significantly as irrigation decreased. Ethanol fermentation efficiency ranged from 90.6% to 91.9% and correlated positively with FAN during the first 30 h of fermentation (R² = 0.926). Deficit irrigation level had a negative impact on ethanol yield. The sorghum with low irrigation yielded about 8.9% less ethanol (434.52 mL ethanol per kg sorghum) than samples with higher irrigation (473.32 mL ethanol per kg sorghum). Residual starch contents in the distillers dried grains with solubles was less than 1% and ranged from 0.70% to 0.84%.
Keywords: Composition; Ethanol yield; Irrigation; Physical properties; Sorghum